Competitive Environment Hypothesis in Turkish Banking System - Aslan, Alper; Koksal, Kemal; Ocal, Oguz (International Journal of Economics and Financial Issues, 2011)
This paper investigates the persistence of profit in Turkish banking system for the period of 2004:1 – 2009:4 by focusing net income after tax to total equity (ROE) as profit measures by utilizing panel unit root tests. We found that competition among surviving banks is high in the Turkish Banking System for the period 2004:1 – 2009:4 which means that competitive environment hypothesis is valid in Turkish banking system. Keywords: Persistence; ROE; Turkish Banking System.